The regulatory impact of a harmonized artificial intelligence regulation proposal on the clinical research landscape in the European Union (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article offers a critical analysis of how the proposed Artificial Intelligence Act (AIA) will support the rights, safety, dignity, and well-being of clinical research participants and ensure the availability of reliable and robust data as described in Clinical Trials Regulation (EU) No. 536/2014. Analysis is focused on how the proposed regulation will impact clinical research conducted within the European Union. The proposed artificial intelligence regulation is evaluated based on what it will bring to the multiple stakeholders in clinical research – including sponsors, investigators, patients, society – and how it would align with the core principles of the Clinical Trials Regulation.
Keywords: Artificial Intelligence; Regulation; Machine Learning; Clinical Trials; Clinical Research